1974
DOI: 10.1080/00288233.1974.10430556
|View full text |Cite
|
Sign up to set email alerts
|

Performance of sheep on New Zealand hill country

Abstract: The growth and composition of 5-, 10-, and 15-month-old Merino, Romney, Corriedale, Perendale, and Border Leicester x Romney wethers on steep New Zealand hill country were studied. The Merinos grew slower than the Romneys and Corriedales, and the Perendales and Border Leicester x Romneys were the fastest-growing breeds, both in terms of live weight and carcass weight. Some benefits to hill country farmers of changing to a faster-growing breed of sheep are discussed.Data are given on the growth of various compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1974
1974
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…The results from this trial have shown, as in the lamb trial of Kirton et al (1974), that higher individual carcess weights were achieved in cull ewes on hill country from the BR than from the RR in the same flock.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The results from this trial have shown, as in the lamb trial of Kirton et al (1974), that higher individual carcess weights were achieved in cull ewes on hill country from the BR than from the RR in the same flock.…”
Section: Discussionsupporting
confidence: 51%
“…Taste panel assessment shows that ewe mutton can be acceptable to consumers as roasting meat, although it has a slightly lower score than those reported for lamb (Kirton et al 1974). …”
Section: Discussionmentioning
confidence: 80%
“…The object of the different levels of nutrition immediately after weaning was to ensure that some lambs showed oestrus while others did not. Nutrition during this period affects the probability of a lamb showing oestrus over and above the nutritional effects on live weight (Moore & Smeaton, 1980 (Kirton, Dalton & Ackerley, 1974 (Kirton & Pickering, 1967 …”
Section: Methodsmentioning
confidence: 99%
“…This paper presents the growth and wool production from five breeds of wethers slaughtered at three ages. The carcass results are presented by Kirton et al (1974) in part II.…”
Section: Introductionmentioning
confidence: 99%